2022
DOI: 10.1177/24715492221142688
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Bacterial Load and Initial Run Time of a Surgical Helmet

Abstract: Background Periprosthetic joint infection (PJI) is a complication of arthroplasty surgery with significant morbidity and mortality. Surgical helmets are a possible source of infection. Pre-existing dust and microorganisms on its surface may be blown into the surgical field by the helmet ventilation system. Methods Twenty surgical helmets at our institution were assessed through microscopy and polymerase chain reaction testing. Helmets were arranged with agar plates under the front and rear outflow vents. Helme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Intraoperatively, many surgeons prefer the use of helmets, but concerns exist with regard to the potential contamination of the fan. One study suggested that the fan should run for 3 minutes prior to entering the operating room to decrease the risk of contamination 17 . We have made great strides reducing the rates of PJI following primary TKA and THA over the last decade, but there is more work to be done.…”
Section: Preventionmentioning
confidence: 99%
“…Intraoperatively, many surgeons prefer the use of helmets, but concerns exist with regard to the potential contamination of the fan. One study suggested that the fan should run for 3 minutes prior to entering the operating room to decrease the risk of contamination 17 . We have made great strides reducing the rates of PJI following primary TKA and THA over the last decade, but there is more work to be done.…”
Section: Preventionmentioning
confidence: 99%